Foreign Language Anxiety in EFL Contexts: Implications for Speaking Performance and Pedagogy - sumirna, sumirna (MACCA : Science-Edu Journal, 2025)
Foreign language anxiety is widely recognized as a crucial factor influencing the oral performance of English as a Foreign Language (EFL) learners. This study aimed to investigate the correlation between students’ anxiety and their speaking performance, focusing on seventh-semester students at the Foreign Language Academy of the Muslim University of Indonesia. Employing a descriptive quantitative method, data were collected through structured questionnaires distributed to 15 participants. The instrument measured anxiety across multiple dimensions, including communication apprehension, fear of negative evaluation, and self-perceived inefficacy, and responses were analyzed using descriptive and correlational techniques. The results indicated a strong negative correlation between students’ anxiety levels and their speaking performance. Students reported heightened nervousness in oral tasks, particularly when required to speak spontaneously or under evaluative scrutiny. Lack of vocabulary and insufficient preparation were identified as primary triggers of anxiety. At the same time, strategies such as preparation, relaxation, and positive thinking were noted as effective though underutilized coping mechanisms. The findings align with international research on foreign language anxiety, while also revealing contextual nuances specific to Indonesian learners. Pedagogical implications highlight the need for supportive classroom practices, peer collaboration, and teacher feedback that fosters psychological safety. The study contributes to the body of knowledge by bridging theoretical perspectives with practical strategies and suggests that future research should focus on longitudinal designs and digital-based interventions to further explore anxiety management. These insights underscore the importance of integrating affective considerations into EFL pedagogy to enhance learners’ oral proficiency.